Aggregation kinetics of microplastics in aquatic environment: Complex roles of electrolytes, pH, and natural organic matter. (June 2018) - Li, Shuocong; Liu, Hong; Gao, Rui; Abdurahman, Abliz; Dai, Juan; Zeng, Feng
Abstract: Microplastics are an emerging contaminants of concern in aquatic environments. The aggregation behaviors of microplastics governing their fate and ecological risks in aquatic environments is in need of evaluation. In this study, the aggregation behavior of polystyrene microspheres (micro-PS) in aquatic environments was systematically investigated over a range of monovalent and divalent electrolytes with and without natural organic matter (i.e., Suwannee River humic acid (HA)), at pH 6.0, respectively. The zeta potentials and hydrodynamic diameters of micro-PS were measured and the subsequent aggregation kinetics and attachment efficiencies (α) were calculated. The aggregation kinetics of micro-PS exhibited reaction- and diffusion-limited regimes in the presence of monovalent or divalent electrolytes with distinct critical coagulation concentration (CCC) values, followed the Derjaguin-Landau-Verwey-Overbeek (DLVO) theory. The CCC values of micro-PS were14.9, 13.7, 14.8, 2.95 and 3.20 mM for NaCl, NaNO3, KNO3, CaCl2 and BaCl2, respectively. As expected, divalent electrolytes (i.e., CaCl2 and BaCl2 ) had stronger influence on the aggregation behaviors of micro-PS as compared to monovalent electrolytes (i.e., NaCl, NaNO3 and KNO3 ). HA enhanced micro-PS stability and shifted the CCC values to higher electrolyte concentrations for all types of electrolytes. The CCC values of micro-PS were lower than reported carbonaceous nanoparticles CCC values. The CCC[Ca 2+ ]/CCC [Na + ] ratios in the absence and presence of HA at pH 6.0 were proportional to Z −2.34 and Z −2.30, respectively. These ratios were in accordance with the theoretical Schulze–Hardy rule, which considers that the CCC is proportional to z −6 –z −2 . These results indicate that the stability of micro-PS in the natural aquatic environment and the possibility of significant aqueous transport of micro-PS. Graphical abstract: Image 1 Highlights: Complex roles of electrolytes, pH, and NOM on the aggregation behavior of micro-PS were firstly evaluated. The increment of CCC values was dominated by the HA coatings on micro-PS. The aggregation kinetics of micro-PS were elucidated by the DLVO theory. The CCC values of micro-PS offered information for the fate of microplastics.